Analysis of the Field of Meaning in Endorsement Product Captions - Syafroni, Roni Nugraha (MULTIPLE: Journal of Global and Multidisciplinary, 2024)
Instagram, a highly popular social media platform in Indonesia, has undergone a transformation, evolving beyond being merely a source of entertainment to serving as a medium for providing education to the public. The term "celebgram" has emerged as a result of competition among product manufacturers striving to boost sales in a practical and economical manner, primarily through endorsements by celebgrams. The objective of this study is to analyze the meaning field inherent in the captions of product photos endorsed by Margaretha Lie. These photos were sourced from her personal Instagram account https://www.instagram.com/margarethalie/?hl=id The research method employed is descriptive qualitative analysis, utilizing literature and documentation techniques for data collection. The data was then analyzed using Chaer's book as the primary reference and other semiotics books as supplementary sources. The findings of this study reveal that the sub-theory of the meaning field, derived from semantic theory, can be established when examining issues beyond spoken language, particularly in the analysis of product captions endorsed by Margaretha Lie. The success of this study lies in the integration of linguistics and social media, a synergy not fully optimized in previous research. In this investigation, it was observed that Margaretha Lie's endorsed products encompassed one photo related to facial care and three photos related to fashion.